(untitled) (Global Journal of Science Frontier Research, 2018)
This is a statistical loom in which to estimate the residual amounts of pesticides with various activities present in environmental samples by employing electro analytical techniques such as adsorptive stripping voltammetry. Average amounts for ten replicates found by applying statistical concepts such as standard deviation and correlation coefficient and in all the findings in this approach all the possible errors are minimised and accuracy is maximised. Water samples of various areas are collected and investigated for pesticide residues before and after the application of pesticides.